Acupuncture PC6 for postoperative nausea and vomiting at different times: A protocol for systematic review and meta analysis. Issue 22 (29th May 2020) - Shi, Kejin; He, Fengyi; Tang, Ying; Xiao, Xiao; Zhang, Jiayuan; Jin, Yuxia; Wang, Yunxia; Zhang, Qi
Abstract: Background: Postoperative nausea and vomiting (PONV) is a condition that commonly following anesthesia and surgery, antiemetics can lead to some side effects in treating PONV. Acupuncture PC6(Neiguan) has been widely used in the prevention and treatment of postoperative nausea and vomiting. However, there still exists controversy towards its effectiveness, appropriate, and effective intervention time. We, therefore, design this meta-analysis to assess the effectiveness and confirm the optimal time of acupuncture PC6 point for PONV. Methods: The following electronic databases will be searched from their inception to April 2020, including PubMed, Cochrane Library, EMBASE, Web of Science, WHO International Clinical Trials Registry Platform, Chinese National Knowledge Infrastructure, WanFang Database, Chinese Biomedical Literature Database, the Chongqing VIP Chinese Science, and Technology Periodical Database. All randomized controlled trials in English or Chinese involving acupuncture PC6 for patients with PONV will be included. Two reviewers will independently responsible for the data extraction, study selection, risk of bias assessment and assessment of study quality. The primary outcome was the number of postoperative nausea, postoperative vomiting and PONV during 0 to 6 hours and after 6 hours of the postoperatively. The secondary outcome is the number of people with side effects and the use of rescue therapy. The meta-analysis will be conducted using RevMan V.5.3.5 statistical software. Results: This systematic review will evaluate the efficacy and appropriateness time of acupuncture PC6 in the treatment of PONV. Conclusion: This study will provide high-quality current evidence of the effectiveness and optimal time of acupuncture PC6 point for the patient with PONV. Ethics and dissemination: Ethical approval is not required; this review will not involve individuals' information. The results will be published in a peer-reviewed publication or disseminated in relevant conferences. INPLASY Registration number: DOI 10.37766/inplasy2020.4.0012